A Reflection on Summer School on the Topic “Women in Europe: an Unfinished Revolution?”: EUROPAEUM, 29th June – 4th July 2014, Universidad Complutense, Madrid - Vrbková, Tereza (Lidé města, 2014)
This short essay is a reflection on one particular student summer school focused on gender topics. The target is not to evaluate summer schools on gender topics in general or to give an objective perspective to this specific summer school but to describe and reconsider the way of presenting the gender phenomenon at this specific school from an anthropology student’s point of view.